Detection of Mesiobuccal Canal in Maxillary Molars and Distolingual Canal in Mandibular Molars by Dental CT: A Retrospective Study of 100 Cases - Sushma Rathi; Jayaprakash Patil; Prashant P. Jaju (International Journal of Dentistry)
Objective. To detect presence of MB2 canal in maxillary molars and distolingual canal in mandibular molars by Dental CT. Material and Methods. A retrospective study of 100 Dental CTs was done. Axial and paraxial images obtained were used to assess the presence of MB2 canal in maxillary molars and distolingual canal in mandibular molars. Results. The youngest patient was of 11 years while the eldest patient was of 77 years. Males were 58 in number and females were 42 in number. MB2 canals were present in 57 patients and distolingual canal was present in 18 patients. Maximum MB2 canals were present in age group between 51 and 60 years, while distolingual canals were present in age group of 21–30 years. Conclusion. Dental CT allows adequate visualization of variation in root canal morphology and can be important diagnostic tool for successful endodontic therapy.